New insights into the limited thermotolerance of anhydrobiotic tardigrades. Issue 1 (1st January 2020) - Neves, Ricardo Cardoso; Stuart, Robyn M.; Møbjerg, Nadja
ABSTRACT: The recent discovery of an upper limit in the tolerance of an extremotolerant tardigrade to high temperatures is astounding. Although these microinvertebrates are able to endure severe environmental conditions, including desiccation, freezing and high levels of radiation, high temperatures seem to be an Achilles' heel for active tardigrades. Moreover, exposure-time appears to be a limiting factor for the heat stress tolerance of the otherwise highly resilient desiccated (anhydrobiotic) tardigrades. Indeed, the survival rate of desiccated tardigrades exposed to high temperatures for 24 hours is significantly lower than for exposures of only 1 hour. Here, we investigate the effect of 1 week of high temperature exposures on desiccated tardigrades with the aim of elucidating whether exposure-times longer than 24 hours decrease survival even further. From our analyses we estimate a significant decrease in the 50% mortality temperature from 63ºC to 56ºC for Ramazzottius varieornatus exposed to high temperatures in the desiccated tun state for 24 hours and 1 week, respectively. This negative correlation between exposure-time and tolerance to high temperatures probably results from the interference of intracellular temperature with the homeostasis of macromolecules. We hypothesize that high temperatures denature molecules that play a vital role in sustaining and protecting the anhydrobiotic state.